Molecular engineering of biomolecules for nanobio-sciences. (22nd February 2010) - Renaudet, Olivier; Garcia, Julian; Boturyn, Didier; Spinelli, Nicolas; Defrancq, Eric; Labbe, Pierre; Dumy, Pascal
Biologically programmed molecular recognition provides the basis of all natural systems and supplies evolution optimised functional materials from self-assembly of a limited number of molecular building blocks. Biomolecules such as peptides, nucleic acids and carbohydrates represent a diverse supply of structural building blocks for the chemist to design and fabricate new functional nanostructured architectures. In this context, we review here the chemistry part of our Nanobio program, we have developed in Grenoble to manipulate such biomolecules, and organic molecules, as well as assemble combinations thereof using a template assembled approach. With this methodology, we have prepared new integrated functional systems exhibiting designed properties in the field of nanovectors, biosensors as well as controlled peptide self-assembly. Thus this molecular engineering approach allows for the rational design of systems with integrated tailor-made properties and paves the way to more elaborate applications by bottom-up design in the domain of nanobiosciences.